The necessary evolution of cybermetrics - Aguillo, Isidro F. (Anuario ThinkEPI, 2012)
The origins, disciplinary relationships and main applications of cybermetrics and webometrics are explained, in order to proceed to a discussion of the current situation regarding the methods used for extracting web information and indicators from publicly available sources. We performed a comparative analysis of three techniques to measure the prestige, impact or visibility of academic institutions, including: 1) the survey, limited by its subjectivity and small sample sizes, 2) citation analysis, also hampered by small populations but which offers more reliability because it relies on peer opinions, and 3) link analysis. Link analysis is considered the cornerstone of webometrics and the large numbers involved is to be appreciated. It can identify patterns despite being the method that is most "noisy" because of the richness and diversity of motivations for linking. The unfortunate demise of Yahoo Site Explorer, the main source of information on links, is reported and its absence will force a rethinking of the techniques and a search for alternative sources of this valuable type of data. Some alternatives are studied, including the use of mentions such as titles, names of institutions or individuals and so-called reference or quote URLs, and their advantages and disadvantages are discussed. It is noted that this new approach is especially useful for web 2.0 tools.
Keywords: Cybermetrics; Webometrics; Links analysis; Search engines; Mentions; Url mentions.